Análisis de disponibilidad hídrica de la microcuenca Curiyacu del distrito de San Antonio provincia de San Martín - Mejia Bardaléz, Alex Darwin (2013)
The following report is based on the study conducted to determine the availabilíty of water resources for water supply for the population ofthe District of San Antonio. Nowadays the attention that requires developing countries ts associated with the sustainability concept. Currently these studies allow optimization of public investment in our country and the natural resources sustainability, in this case the sustainable use of water resources ofthe Micro watershed ofCuriyacu. To comply or try to achieve conception has worked with historical precipitation data for subsequent statistical study and the field visit Curiyacu Micro watershed and on-site measurement of flow, working these data to determine the Water A vailability and perform Hydrological Balance Micro watershed study.